ANALISIS KESTABILAN LERENG MENGGUNAKAN DATA VWP (VIBRATING WIRE PIEZOMETER) PADA PT.NEWMONT NUSA TENGGARA NUSA TENGGARA BARAT (Jurnal Geomine, 2015)
Slope stability that is important of open pit system . The aims of this research todetermine the influenceof groundwater pressureto the value of safety factorfrom some slope in phase5 to getstable slope conditions when ultimate pit reach phase6. Data of Groundwater obtained from the data of VWP (Vibrating Wire Piezometer). This analysis was conducted using GLE/Morgenstern-price and bishops simple. Analysis methods that using on the model is  pressure drop testing from each censor and pressure drop in the horizontal depth. Analysis picture simulation from safety factor is 1.308 pressure drop 25 meter at pressure 400 Kpa, pressure 450 Kpa, FK 1.211, 500 Kpa, FK 1,001 and pressure drop 50 meter only pressure different however whit same safety factor is 800 Kpa, 900 Kpa, 1000 Kpa. General conclusions based on the result of research found that the effect of water pressure on slope safety factor, more big of groundwater pressureso descend slope value of safety factor. By reducing the water pressure on a wall slope it means increase the value of the slope safety factor.